The continuity psychiatric nursing care model to enhance medication adherence in schizophrenia patients in Indonesia: Participatory action research - Sri Wahyuni; Wandee Suttharangsee; Orawan Nukaew (Journal of the Pakistan Medical Association, 2024)
Objective: To develop a continuity of psychiatric nursing care model to enhance medication adherence in schizophrenia patients. Method: The Participatory Action Research study was conducted from 2017 to 2018 in Pekanbaru, Riau, Indonesia, after approval form the ethics review committee of the Faculty of Nursing, Prince of Songkla University, Thailand. The sample included schizophrenia inpatients at a mental hospital, their family members and nursing staff. Qualitative data were gathered through in-depth interviews, observations, field notes, and photo records. Data was subjected to content analysis, while trustworthiness of the model was also determined. Results: Of the 57 subjects, 22(38.6%) were schizophrenia patients, 22(38.6%) were family members, and 13(22.8%) were nurses. The continuity of psychiatric nursing care model consisted of three components: preparing for readiness to live a normal way of life; creating a supportive environment; and, sustaining the continuity of care until the community level care. Conclusion: The continuity of psychiatric nursing care model facilitated holistic nursing care aspects. Keywords: Continuity of care, Medication Adherence, Participatory action research, Schizophrenia.